Preliminary experiments on technologies for satellite orbital maintenance using Micro-LabSat 1 - Kimura, Shinichi; Mineno, Hitoshi; Yamamoto, Hiroshi; Nagai, Yasufumi; Kamimura, Heihachiro; Kawamoto, Satomi; Terui, Fuyuhito; Nishida, Shin-Ichiro; Nakasuka, Shinichi; Ukawa, Shinichi; Hashimoto, Hidekazu; Takahashi, Nobuhiro; et al. (Advanced robotics, 2004)
For maturation of space activities, not only developing and using space systems is important, but also performing maintenance on them in their orbital environment is necessary in order to use them efficiently. The Communications Research Laboratory (CRL) has been studying an orbital maintenance system (OMS), specifically an on-orbit satellite maintenance system. An important first step is the capability to autonomously recognize and rendezvous with a target satellite. The CRL developed a microprocessor multi-chip module to control the OMS, including its robotic system and image processing, and installed it on Micro-LabSat for a mission called Micro-OLIVe (MicroLabSat was developed by NASDA and launched in 2002 together with the environment observation technology satellite ADEOS-II). In this paper, we describe the OMS concept, our experimental system and results of the Micro-OLIVe experiments. These experiments aimed at using the microprocessor multi-chip module to control the OMS, its camera units that use conventional C-MOS digital still cameras and its software used for flexible image processing.